A experiência do corpo-texto : um aceno à construção da cena no corpo e à reinvenção do corpo em cena - Bellicieri, Fernanda Nardy (2016)
The thesis aims to describe an authorial transcription methodology which I call "bodytext" (verb in its emetic quality) to a "text-body" or scene, re-calculated, rescued and resulting from this organic-performative verb, a phenomenon residue; being both concepts, “body-text” and “text-body" anchored in Merleau Ponty's existentialism. A scenic process "derived from" and "deriving in" an individual perception in its contextual space-time, being all (individual, space, time and process) structurally algorithmic-dependents; so metaphorically, in considering the scene transcription emphasizing analogical language; as syntactically, in case of scene expansion by digital language, appoaching it (the scene) to a performative concept, subjectivized, responsive to current time. In its essentially theoretical-practical feature, by authorial works analysis, the thesis outlines some possible relationships between parameters stabilished like important variables concerning scenic transcription process (Stage type, Authorship, Time exposure to character and Narrative decating in codes and dramatic units). Variables of a process in which a performative verb, or an authorinterpreter current intention language residue reaches the scene, aestheticised (as part crystallized) and mythical (as inevitably ephemeral) and expanded beyond verbal language. At the end of the thesis a File Theatre performance will be proposed: a scene or ambience that algorithmically embodies its intentionality in real time by using generative software fed with contextual files, destituted from their hierarchical language function, since expanded as digital files.